The Moderating Role of Firm Size on the Association between Managerial Ability and Tax Avoidance - Saragih, Arfah Habib; Raya, Mutya Nurmala; Hendrawan, Adang (Universitas Pendidikan Indonesia, 2021)
Changes in taxation policies generate uncertainty for companies that can potentially encourage companies perform more aggressive tax planning. Aggressive tax planning can lead to tax avoidance. This study aims to investigate the effect of managerial ability, firm size, and the interaction of managerial ability with firm size on corporate tax avoidance practices. The study used quantitative method, with panel data linear regression model, random effects method, with a time period of 2009-2019. The results of this study indicate that managerial ability, firm size, and its interaction have a significant impact on corporate tax avoidance. This research is expected to contribute in enriching the literature on the effect of managerial ability on tax avoidance, particularly in Indonesia.